EXPLORING FATHERHOOD VALUES IN “THE PURSUIT OF HAPPYNESS” MOVIE AND THEIR IMPLICATIONS FOR ENGLISH LANGUAGE TEACHING IN INDONESIAN CONTEXT - Kedang, Intan Febriantari Putri; Siti Maysuroh; Yulia Agustina; Ari Prasetyaningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Character education and fatherhood figures are crucial for a child’s moral development, yet their integration into English Language Teaching (ELT) via multimodal films remains underexplored in Indonesia. This study aims to identify the fatherhood values represented in the movie The Pursuit of Happyness (2006) and analyze their implications for ELT practices. Employing a qualitative descriptive design and content analysis, data were collected from 21 scenes depicting the protagonist’s verbal and non-verbal actions based on Lamb’s (2010) framework. The findings reveal four integrated fatherhood values: responsibility (5 scenes), sacrifice (6 scenes), care (5 scenes), and perseverance (5 scenes). These values operate not as isolated traits, but as a unified system where responsibility motivates sacrifice, which is sustained by emotional care, ultimately culminating in relentless perseverance. In conclusion, the film represents a holistic paternal identity that provides robust thematic anchors for character-based ELT activities, such as analytical writing and role-playing. Utilizing this movie as a learning medium supports the Indonesian Merdeka Belajar curriculum by simultaneously enhancing students’ communicative language proficiency and moral awareness.